Answer : The logarithmic equation of given exponential equation is, [tex]\ln (0.0183)=-4[/tex]
Step-by-step explanation :
As we are given the exponential equation.
[tex]e^{-4}=0.0183[/tex]
Formula used :
The inverse property of logarithm for the expression [tex]\ln e^x[/tex] is:
[tex]\ln e^x=x[/tex]
Now we have to determine the logarithmic equation of given exponential equation.
[tex]e^{-4}=0.0183[/tex]
Taking natural logarithm both sides as,
[tex]\ln e^{-4}=\ln (0.0183)[/tex]
[tex]-4=\ln (0.0183)[/tex]
[tex]\ln (0.0183)=-4[/tex]
Thus, the logarithmic equation of given exponential equation is, [tex]\ln (0.0183)=-4[/tex]